2019
DOI: 10.21873/cgp.20146
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptomic Analysis of Apigenin on TNFα Immuno-activated MDA-MB-231 Breast Cancer Cells

Abstract: Background: Triple-negative breast cancer is categorized by a lack of hormone receptors, inefficacy of antiestrogen or aromatase inhibitor chemotherapies and greater mortality rates in African American populations. Advancedstage breast tumors have a high concentration of tumor necrosis factor-α (TNFα) throughout the tumor/stroma milieu, prompting sustained release of diverse chemokines (i.e. CC motif chemokine ligand 2 (CCL2)/CCL5). These potent chemokines can subsequently direct mass infiltration of leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
0
20
1
Order By: Relevance
“…Our finding was consistent with the result of the previous BC studies in terms of the ability of CXCL11 to promote tumor cell migration and invasion phenotypes. 22,24,25 Besides, we found that miR-1298-5p was the upstream miRNA of CXCL11 and that it could inhibit CXCL11 expression by binding to CXCL11 3ʹUTR, a result that was different from that of the previous study.…”
Section: Discussioncontrasting
confidence: 79%
“…Our finding was consistent with the result of the previous BC studies in terms of the ability of CXCL11 to promote tumor cell migration and invasion phenotypes. 22,24,25 Besides, we found that miR-1298-5p was the upstream miRNA of CXCL11 and that it could inhibit CXCL11 expression by binding to CXCL11 3ʹUTR, a result that was different from that of the previous study.…”
Section: Discussioncontrasting
confidence: 79%
“…In some tumors a great concentration of tumor necrosis factor α (TNF α) protein was found and transcriptomic analysis has demonstrated that apigenin is able to downregulate half of the genes that normally are upregulated by TNFα, all related to tumor promotion, invasion, and metastatic growth [108]. Interleukin-6 (IL-6) is another protein whose expression is negatively regulated by apigenin and the reduced expression affects not only tumor proliferation, but also migration and invasiveness [109].…”
Section: Apigeninmentioning
confidence: 99%
“…Tumor-infiltrating lymphocytes (TILs) and tertiary lymphoid structures (TLSs) have favorable prognostic value in TNBC [ 20 ]. The immune response in tumors is mainly dependent on adaptive immunity mediated by T cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%